The Right to Read: Children’s Rights and Children’s Publishing in Britain - Lucy Pearson (Strenae)
As protesters filled Paris streets in May ‘68, across the Channel a quieter revolution was taking place. A radical reshaping of British education during the post-war era laid the way for a new era of progressive thinking about childhood, and turned attention to the question of children’s rights. Central to this was the notion of a right to read, and of the right of children to books which recognised the realities of their lives. Leila Berg – activist, author, editor – was at the forefront of this movement with her series of early reader Nippers. This paper examines Nippers in context, showing how the books brought together a long tradition of activist thought and encapsulated much of the spirit which animated ’68 more broadly.